DESIGN OF UNDER-FREQUENCY LOAD-SHEDDING AND ISLAND OPERATION DEFENSE SCHEMES IN THE SOUTHERN SULAWESI INTERCONNECTION SYSTEM - Fedrico Simorangkir, Jonathan
The electric power system cannot be separated from the risk of disturbances, both minor disturbances (fluctuations in load power) and severe disturbances (trips of generating units, transformers, or transmission lines). Disturbances in the power system can affect the balance of power between generation and load so that it can have an impact on disrupting system stability. If disturbance which causes the system experiencing a contingency occurs, which also causes a decrease in active power generation in the system, the system frequency may fall towards instability if corrective action is not taken on the system by isolating the disturbance and returning system operation to normal conditions. The application of Under Frequency Load Shedding (UFLS) scheme is a solution for system with under-frequency condition. The UFLS scheme is generally divided into several stages with different frequency threshold values. If the system frequency detected by the Under Frequency Relay (UFR) drops past the threshold value at a certain stage, the UFR will execute load shedding according to the load quota/volume that has been initialized in the UFLS scheme. In this research, a study will be carried out to determine the impact of implementing the UFR-based UFLS scheme on the South Sulawesi (Sulbagsel) interconnection system. The results obtained in this study are the design of the UFLS scheme proposed to be applied to the Sulbagsel System, both in the Island Operation and Multi-stages UFR schemes, can increase the resilience of the Sulbagsel system to maintain frequency stability after severe disturbances occur in the system.